2011
DOI: 10.1038/jid.2010.264
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation, Mental Health Problems, and Social Impairment Are Increased in Adolescents with Acne: A Population-Based Study

Abstract: We performed a cross-sectional, questionnaire-based study to explore the relationship of suicidal ideation, mental health problems, and social functioning to acne severity among adolescents aged 18-19 years. A total of 4,744 youth were invited and 3,775 (80%) participated. In all, 14% reported having substantial acne (a lot and very much). Among those with very much acne, as compared those with no/little acne, suicidal ideation was twice as frequently reported among girls (25.5 vs. 11.9%) and three times more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
272
3
18

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(315 citation statements)
references
References 48 publications
7
272
3
18
Order By: Relevance
“…The problem of acne is not only visual, as many people think, but it can also trigger many psychological disturbances, which might even have fatal outcomes [1,2]. This common disease affects more than 90% of males and 80% of females [3] and it is also a skin disorder with a huge impact on the quality of life [4].…”
Section: Discussionmentioning
confidence: 99%
“…The problem of acne is not only visual, as many people think, but it can also trigger many psychological disturbances, which might even have fatal outcomes [1,2]. This common disease affects more than 90% of males and 80% of females [3] and it is also a skin disorder with a huge impact on the quality of life [4].…”
Section: Discussionmentioning
confidence: 99%
“…De los estudios comunitarios realizados en Noruega 4,6 y otros países [7][8][9] , sabemos que los individuos con picazón en la piel, eccema y psoriasis tienen el doble de probabilidades de estar deprimidos que la población en general 10 . Se ha demostrado que la depresión comórbida, la ansiedad y la ideación suicida son comunes en pacientes con afecciones cutáneas 11 .…”
Section: Impacto Psicológico Del Cáncer De Piel En La Vejezunclassified
“…This study also suggested that acne in adults is a disorder that has both medical and psychomatic characteristics 6 . In 2011, Halvorsen et al 7 reported that among 3775 adolescents aged 18-19 years, 14% had severe acne, in which one in every four adolescents reported suicidal thoughts. Hence, suicidal ideation was reported two times more in females with acne than those without acne and three times more in male patients 7 .…”
mentioning
confidence: 99%
“…In 2011, Halvorsen et al 7 reported that among 3775 adolescents aged 18-19 years, 14% had severe acne, in which one in every four adolescents reported suicidal thoughts. Hence, suicidal ideation was reported two times more in females with acne than those without acne and three times more in male patients 7 . Hence, acne leads to suicidal ideation due to emotional distress and society anxiety 8 .…”
mentioning
confidence: 99%